Dharmagitha as a Strategy for Character and Skills Education Based on Local Wisdom in the Elementary School - Luwih, I Made (Jayapangus Press, 2025)
Character education and 21st-century skills are urgent needs in Indonesia’s basic education system. In the context of Balinese culture, Dharmagitha is a sacred chant rich in Hindu ethical and spiritual values, with great potential as an educational medium steeped in local wisdom. This study aimed to examine the role of Dharmagitha as a learning strategy that can shape the noble character and basic skills of elementary school students. Through a descriptive qualitative approach, this study revealed that the integration of Dharmagitha in learning activities not only strengthens students’ cultural identity and spirituality but also fosters values of discipline, responsibility, cooperation, as well as literacy and musicality. Additionally, this strategy encouraged students to engage in contextualized, fun, and meaningful learning. Thus, Dharmagitha has proven to be an effective alternative strategy for character and skills education, grounded in local wisdom, making it relevant to today’s educational needs.